ANALISIS LINGKUNGAN PENGENDAPAN BATUGAMPING BERDASARKAN DISTRIBUSI UNSUR KIMIA DI DAERAH CIDORA, KECAMATAN AJIBARANG, KABUPATEN BANYUMAS , JAWA TENGAH - Fauzielly, Lili; Hamdani, A. Helman (Bulletin of Scientific Contribution, 2015)
Studies on the distribution of chemical elements Lawangdora limestone area has been conducted to determine the depositional environment is based on the chemical characteristics . The purpose of this study was to apply the theory of Chilingar who stating that Mg levels will decrease when deposited away from the beach. The results showed that the study area is dominated by calcite limestone, and the type is low magnesium calcite . This is a type of calcite carbonate in deep marine sediments. Based on the cross section of the direction and distance relative to the content of the element magnesium ( Mg ) is seen that the direction of deepening moves relative to the north.